Criminal Law Accountability of Sexual Stalking Perpetrators Through Social Media - Ayu Dian Ningtias; Kristiya Lutfiasandhi; Fajar Seto Nugroho; Khofifah Nur Ayni (Universitas Islam Lamongan, 2026)
Sexual stalking is a new form of crime that has emerged along with the development of technology. In the past, stalking was done directly, such as following the victim. However, now, stalking can occur in the digital world, especially through social media. Perpetrators can easily access the victim's personal information, send sexually suggestive messages, or carry out other disturbances without meeting in person. This study aims to understand in depth the legal protection mechanism for victims and the form of criminal liability for perpetrators of sexual stalking through social media. This research method uses a normative juridical research type, with a legislative approach and a conceptual approach. The results of this study conclude: that legal protection for victims of sexual stalking through social media can be in the form of preventive legal protection and repressive legal protection. Meanwhile, the criminal legal liability, perpetrators of sexual stalking through social media can be subject to criminal sanctions in the form of imprisonment, fines, and/or other actions as stipulated in applicable laws and regulations. However, there are exceptions in certain conditions that cause a person not to be held accountable for their actions.